Procalcitonin levels in COVID-19 patients - Hu, Rui (Int J Antimicrob Agents, 2020)
Coronavirus disease 2019 (COVID-19), caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been declared a pandemic. This study analysed 95 SARS-CoV-2-infected patients, including 62 moderate COVID-19 patients, 21 severe COVID-19 patients and 12 critical COVID-19 patients (6 patients died, all critical). The results showed that the mean serum procalcitonin (PCT) levels were over four times higher in severe patients than in moderate patients and were over eight times higher in critical patients than in moderate patients. For discharged patients, both high-normal PCT levels and abnormal PCT levels decreased during recovery. However, in death cases, serum levels of PCT increased as the disease worsened. We demonstrate that PCT may be an indicator of disease severity in COVID-19 and may contribute to determining the severity of patients infected with SARS-CoV-2. Moreover, serial PCT measurements may be useful in predicting the prognosis.